An Ordinance To Regulate the Sale, Storage, and keeping of Gunpowder and other Explosive and Dangerous Materials, within the limits of the City of Bayonne, §1-5 (NJ, 24 Nov., 1877). - (:unkn) unknown (General Publisher, 1877)
Regulated the storage and sale of gunpowder in the city of Bayonne
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER